Zeolite science 1994 : recent progress and discussions : supplementary materials to the 10th International Zeolite Conference, Garmisch-Partenkirchen, Germany, July 17-22, 1994 - International Zeolite Conference 1994 : Garmisch-Partenkirchen, Germany); Karge, H. G. (Hellmut G.); Weitkamp, J. (Jens); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1995)
This book is a supplementary volume to J. Weitkamp et al. (Editors), Zeolites and Related Microporous Materials: State of the Art 1994 - Proceedings of the 10th International Zeolite Conference, Garmisch-Partenkirchen, Germany, July 17-22, 1994. The larger part of this supplementary volume contains full texts of the Recent Research Reports, which were presented as posters, and the discussions of all the lectures and posters. One full paper is included, because one page was missing in the version published in the Proceedings. A complete list of participants is also included.
Front Cover; Zeolite Science 1994: Recent Progress and Discussions; Copyright Page; Table of Contents; Preface; List of Sponsors; Welcome Address; Breck Award 1994; IZA Award 1994; Election of Professor R.M. Barrel F.R.S., as Honorary President of the Imemational Zeolite Association; After Dinner Speech given by C.T. O'Connor at the Congress Banquet; List of Recent Research Reports; Chapter 1. Recent Research Reports; Full-Length Paper "Alkylation of aniline with methanol on Beta and EMT zeolites exchanged with alkaline cations"; Index of Authors of Recent Research Reports.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Zeolites -- Congresses; Molecular sieves -- Congresses; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Molecular sieves; Zeolites; Ceramics; Electronic books